Comparing an Individual Limited Liability Company in Indonesia and a Single-Member Limited Liability Company Owned by an Individual in Vietnam - Pangesti, Shinta; Pasaribu, Debora; Puteri, Elisabeth Ryanthie Maya (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The recognition of Individual LLCs is a concrete step from the government to support micro and small enterprises, which triggers Indonesia's economic growth. However, improvements to the regulation of Individual LLCs are needed immediately. Purposes of the Research: The research aims to explain and analyze the regulatory comparison of an Individual LLC in Indonesia and a Single-Member LLC owned by an Individual in Vietnam.Methods of the Research: The type of research is normative legal research with statutory and comparative approaches. Data was collected using library research with qualitative analysis.Results of the Research: The results can see from various aspects, such as the definition, company establishment, organizational structure, rights and obligations of company founders, and conversion. In Indonesia, the definition is outlined in Regulation of the Minister of LHR Number 21/2021, while in Vietnam is regulated in Law on Enterprises 2020. An Individual LLC in Indonesia can only establish by an individual, whereas in Vietnam, the owner of the Single-Member LLC can be an organization or an individual. Indonesia only knows the Company's Director, while there are President and a Director/General Director in Vietnam. The rights and obligations of the owner of an Individual LLC in Indonesia are not explicitly regulated, while Vietnam regulates it. It's possible to convert only an Individual LLC into a Capital Partnership LLC in Indonesia, while in Vietnam, it is possible to change either way. Evaluation and improvement of the regulation of Individual LLCs in Indonesia are urgently needed to create a firm legal umbrella for micro and small business actors.